PANDANGAN ISLAM TENTANG HAK ASASI MANUSIA DALAM AL-QUR’AN - Alviana Resthy Inda Hidayat; Amira Meina Zaroh; Ayip Jamalullael (Melati Institute, 2023)
Human rights are the most basic rights bestowed by Allah SWT. towards humans. Al-Qur'an becomes the basis for all elements of human life, including human rights. Historically, the Koran predates the United Nations Declaration of Human Rights. HAM itself is widely discussed in the Qur'an and Sunnah. The principles of human rights in the Qur'an can be elaborated into three, namely al-istiqrar, namely the right to live on the earth until death picks up, al-istimta', namely the right to explore the carrying capacity of life and al-karamah, namely the honor that identical to each individual but has social implications, because self-respect can only work if there are other people who respect one's human dignity, then this al-karamah then gives birth to equal rights. This research was compiled using the qualitative library research method, namely collecting data by finding sources and then editing from various sources such as books, journals, or from existing research. As for the interpretation of the verses, we use the maudhu'i interpretation method, which is a method of searching for answers based on the themes in the Qur'an. The method is to collect verses related to the theme to be discussed, then these verses are compiled and elaborated on asbabun an-nuzul also looking for the linkages of these verses with other verses until then interpreted by taking the opinions of commentators.